Unknown components of the plastidial permeome - Pick, Thea R.; Weber, Andreas P. M. (Frontiers in Plant Science, 2014)
Beyond their role in photosynthesis plastids provide a plethora of additional metabolic functions to plant cells. For example, they harbor complete biosynthetic pathways for the de novo synthesis of carotenoids, fatty acids, and amino acids. Furthermore plastids contribute important reactions to multi-compartmentalized pathways, such as photorespiration or plant hormone syntheses, and they depend on the import of essential molecules that they cannot synthesize themselves, such as ascorbic acid. This causes a high traffic of metabolites across the plastid envelope. Although it was recently shown that non-polar substrates could be exchanged between the plastid and the ER without involving transporters, various essential transport processes are mediated by highly selective but still unknown metabolite transporters. This review focuses on selected components of the plastidial permeome that are predicted to exist but that have not yet been identified as molecular entities, such as the transporters for isopentenyl diphosphate (IPP) or ascorbic acid.